An empirical analysis of the effects of Syrian refugees on the Turkish labor market - Ken Suzuki; Saumik Paul; Takeshi Maru; Motoi Kusadokoro (Asian Development Bank Institute (ADBI), 2019)
This study examines the effects of the recent influx of Syrian refugees on the Turkish labor market. Exploiting this natural experiment, we estimated the causal impacts of involuntary migration on labor market outcomes. We selected the five refugee-hosting regions with the highest number of refugees as treatment regions and four comparable regions with a low refugee-to-population ratio as control regions. Using a difference-in-differences estimation, we found that informal Turkish workers in the refugee-hosting regions were about 4% more likely to leave their job than workers in regions that did not widely host refugees. Such negative impacts on labor market outcomes became larger in 2014-2015 compared with 2012-2013. Furthermore, while females and older workers withdrew themselves from the labor market, males and younger workers become unemployed after the refugee influx.
Keywords: F22; J00; 330; refugee; migration; Syria; Turkey; difference-in-differences estimation